1999
DOI: 10.1038/sj.sc.3100854
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic assessment during intravesical infusion of capsaicin for the treatment of refractory detrusor hyperreflexia

Abstract: Purpose: Parameters to predict outcome and the urodynamic e ects during infusion of capsaicin, seem not to have been assessed in patients with chronic cord injury. We monitored bladder activity urodynamically during infusion of high dosage of capsaicin. Material and methods: Thirty patients, 18 women and 12 men (average age 29 years, range 20 ± 59 years), su ering from chronic spinal myelopathy, who presented a refractory detrusor hyperre¯exia, were studied. They received saline solution containing 10 73 M cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
(15 reference statements)
2
6
0
Order By: Relevance
“…Data which may explain the reasons for the ineffectiveness of resiniferatoxin in treating DO are limited. That vanilloid‐sensitive fibres are not predominant in mediating detrusor reflex, and inadequate desensitization of vanilloid receptors on sensory fibres might be responsible for the poor therapeutic results [25]. A previous study showed that patients with an initial detrusor response of high‐amplitude detrusor contractions with a gradually disappearing contractility have a favourable therapeutic outcome from resiniferatoxin, suggesting adequate desensitization can provide effective suppression of DO caused by vanilloid receptor over‐expression [3,25].…”
Section: Discussionmentioning
confidence: 99%
“…Data which may explain the reasons for the ineffectiveness of resiniferatoxin in treating DO are limited. That vanilloid‐sensitive fibres are not predominant in mediating detrusor reflex, and inadequate desensitization of vanilloid receptors on sensory fibres might be responsible for the poor therapeutic results [25]. A previous study showed that patients with an initial detrusor response of high‐amplitude detrusor contractions with a gradually disappearing contractility have a favourable therapeutic outcome from resiniferatoxin, suggesting adequate desensitization can provide effective suppression of DO caused by vanilloid receptor over‐expression [3,25].…”
Section: Discussionmentioning
confidence: 99%
“…All patients presented detrusor hyperreflexia refractory to oral and/or intravesical oxibutynin and they displayed high voiding pressure associated with frequent urine leakage. The inclusion criteria for the patients' enrollment have been reported previously [8].…”
Section: Capsaicinmentioning
confidence: 99%
“…De Ridder et al [20] reported that repeated instillations of intravesical capsaicin were effective in about 80% of patients with bladder overactivity due to spinal cord disease, with the benefi cial effect lasting 3 to 5 years. At the end of the 1990s, we questioned the effi cacy and safety of capsaicin for the management of detrusor hyperrefl exia [21]. Petersen et al [22] demonstrated in a placebo-controlled crossover study that intravesical treatment with capsaicin did not show benefi cial effects on detrusor hyperrefl exia and produced signifi cant reactive changes in the bladder mucosa.…”
Section: Afferent Innervations: a New Target For The Treatment Of Lutsmentioning
confidence: 99%